The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11999-009-0718-9
|View full text |Cite
|
Sign up to set email alerts
|

Is it Possible to Treat Recurrent Clubfoot with the Ponseti Technique After Posteromedial Release?: A Preliminary Study

Abstract: The Ponseti technique for treating clubfoot has been popularized for idiopathic clubfoot and more recently several syndromic causes of clubfoot. We asked whether it could be used to treat recurrent clubfoot following failed posteromedial release. We retrospectively reviewed 58 children (83 clubfeet) treated by the Ponseti technique for recurrent deformity after posteromedial release in three centers. The minimum followup was 24 months (average, 45 months; range, 24-80 months). We determined initial and final P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…With respect to the non-compliance rate and relapse rate, a variety of medical centers and researches reported different findings. Many authors reported that brace intolerance ranges from 0% to 51% 3,6,7,8,10,20,25,27). In the research by Haft et al,25) the non-compliance rate was 49% and patients who did not adhere to the bracing protocol were 5 times more likely to have a relapse in comparison with children who wore the brace regularly.…”
Section: Relapse After Full Correction and Non-compliance With Brace mentioning
confidence: 99%
“…With respect to the non-compliance rate and relapse rate, a variety of medical centers and researches reported different findings. Many authors reported that brace intolerance ranges from 0% to 51% 3,6,7,8,10,20,25,27). In the research by Haft et al,25) the non-compliance rate was 49% and patients who did not adhere to the bracing protocol were 5 times more likely to have a relapse in comparison with children who wore the brace regularly.…”
Section: Relapse After Full Correction and Non-compliance With Brace mentioning
confidence: 99%
“…Nagaraju report that when treating 18 feet from 13 patients via the Ponseti method, they achieve well-formed plantigrade feet where previously they had used the Kite method and experienced recurrences of the disease [27]. Nogueira reports that for patients who had unsuccessful surgical treatments, 71 out of 83 feet (86%) were corrected with the Ponseti method and the patients developed plantigrade, fully corrected feet [28]. Recurrences of the deformity are characterized as metatarsus adductus, abduction of foot, loss of dorsiflexion, and dynamic supination, which appears during gait analysis when the patient is walking.…”
Section: Citation: Sayit E Sayit At (2015) Clinical Experiences and mentioning
confidence: 99%
“…94 The Ponseti method 1,4,53 , composed basically of manipulations and serial plaster cast changes, percutaneous sectioning of the calcaneal tendon and use of abduction orthosis, has become the preferential method for the treatment of idiopathic CC in many countries, in the last ten years (Bor; Bor, 2002). With widespread acceptance, it was extended for use on older children [95][96][97][98] ; complex and resistant feet 99 ; relapsed feet 100 , including relapses after extensive surgical release 101 , and also, in non-idiopathic cases, such as in myelomeningocele 102,103 and distal arthrogryposis 104,105 . The grounds of the manipulation technique consist of correcting deformities by means of the plastic change of the contractured and shortened elements, which have a high elastic capacity in the younger child.…”
Section: Ponseti's Methodsmentioning
confidence: 99%
“…However, the upper age limit, both for treatment using the Ponseti method, and for the performance of percutaneous tenotomy, is not well established. The use of the Ponseti method was also extended to relapsed feet, including after surgical releases, with reports of good outcomes 101 .…”
Section: Older Children and Relapsed Feetmentioning
confidence: 99%